Integrability and cosmological solutions in Einstein-æther-Weyl theory - Andronikos Paliathanasis; Genly Leon (European Physical Journal C: Particles and Fields, 2021)
Abstract We consider a Lorentz violating scalar field cosmological model given by the modified Einstein-æther theory defined in Weyl integrable geometry. The existence of exact and analytic solutions is investigated for the case of a spatially flat Friedmann–Lemaître–Robertson–Walker background space. We show that the theory admits cosmological solutions of special interests. In addition, we prove that the cosmological field equations admit the Lewis invariant as a second conservation law, which indicates the integrability of the field equations.